Satisfaction of Service Recipients on Quality of Service of Research Clinic, Suranaree University of Technology Hospital - Sinthusopa, Waraporn; Ongsricharoenbhorn, Sayah; Teangphuck, Punyaphat; Tiptawee, Siriporn; Nimkuntod, Porntip (NU Journal of Nursing and Health Sciences, 2024)
This descriptive research aimed to study the level of satisfaction of service recipients on quality of service of research clinic, Suranaree University of Technology Hospital and compare satisfaction of service recipients on quality of service of research clinic classified by personal characteristics. The sample were 44 service recipients who registered to use services at the research clinic. The research instruments were a self-administered questionnaire which consist of 1) Personal information questionnaire and 2) Satisfaction questionnaire. The second set of questionnaires was checked for content validity by 3 experts, with index of item objective congruence more than 0.6 for every item, Cronbach’s alpha reliability was 0.90. Frequency, percentage, mean, standard deviation and Mann-Whitney U Test were used for data analysis.The results revealed that the level of satisfaction of service recipients on quality of service of research clinic overall it was at a high level (x̄ = 4.15, S.D. = 0.532). The service personnel aspect had the highest average and was at the highest level (x̄ = 4.61, S.D. = 0.543), followed by the location and facilities aspect, the average was at a high level (x̄ = 4.25, S.D. = 0.705) in terms of service processes and procedures aspect, the average was at a high level (x̄ = 4.18, S.D. = 0.679). In information resources aspect, the average was at a high level (x̄ = 3.92, S.D. = 0.718) and the public relations aspect, the average was at a high level (x̄ = 3.78, S.D. = 1.011), respectively. And found that service recipients had different personal characteristics including gender, status, educational level, research role, research experience, and the number of times the service was received. There was no difference in satisfaction with the service quality of the research clinic at the 0.05 level. Therefore, it can be concluded that service recipients are treated as individuals using the same standards of service equally provided by personnel providing services at the research clinic.